PENERAPAN METODE WEIGHTED PRODUCT DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP BERBASIS WEB - Nur Arifah Syafitri; Sutardi Sutardi; Anita Puspita Dewi (Informatics Engineering Department of Halu Oleo University, 2016)
Lack of knowledge and information of laptop specifications make common people who want to buy a laptop feel confused to decide which laptop that suits their needs. One way to help prospective buyers in order to select a laptop that suits their needs is to build a system with a web-based decision support system Weigthted Product is a method that uses multiplication to connect the attribute value, where the value should be raised to advance with the corresponding attribute weights. Weighted Product (WP) is part of the concept of Multi-Attribute Decision Making (MADM) where normalization is necessary in the calculation. This system requires the input of weighting value based on the needs of prospective buyers in the form of price, RAM capacity, type of processor, hard drive capacity, and Video Grapphics Array (VGA). The result of this research is to give suggestions on laptops based on the specifications described by the perspective buyer with 100% accurate calculations, either manually or within the decision-support system. Keywords— Decision Support System, Laptop Selection, Weighted Product